FATNESS OF THE CLAM, MERETRIX CASTA (CHEMNITZ) - Durve, V S; Dharmaraja, S K (Indian Journal of Fisheries, 2011)
The quality of the clam Meretrix casta from two different localities at Athankaraiestuary and marine fish farm at Mandapam was assessed by three methods. It was foundthat clams inhabiting Athankarai estuary were of better quality than those from the fishfarm. The probable caiise appears to be the better nutritional conditions in the naturalhabitat of Athankarai estuary along with the free-flowing water and moderate salinityprevailing there.